Tinjauan Kriminologis Terhadap Kasus Bunuh Diri Yang Terjadi Di Kota Kupang - Sonatha, Neni; Manafe, Deddy R. CH.; Fanggi, Rosalind Angel (Law Faculty, Nusa Cendana University, 2025)
This study aims to analyze the factors causing suicide in Kupang City from a criminological perspective, focusing on three suicide cases that occurred among students. The method used in this study is a qualitative approach, which includes case studies, in-depth interviews with the victim's family, and analysis of official documents. The results of the study indicate that suicide is influenced by several factors, including academic pressure such as study load, thesis revision, and demands from lecturers; conflict within the family including forced choice of college major and discriminatory treatment; and psychological disorders such as depression and feelings of isolation. Based on Durkheim's theory, these cases can be categorized as anomic suicide, which is caused by difficulty adapting to academic pressure, and fatalistic suicide related to excessive family control. The most common methods used in these cases are hanging and jumping from bridges, which reflect the ease of access to tools and the geographical conditions in the area. To prevent similar incidents, multidisciplinary collaboration is needed that includes counseling services on campus, strengthening communication within families, community support programs, and policy interventions from the police and government. This study emphasizes the importance of a holistic approach in addressing the problem of suicide, by combining psychological, social, and institutional aspects.